2022
DOI: 10.1111/cts.13372
|View full text |Cite
|
Sign up to set email alerts
|

Liquid biopsy‐based targeted gene screening highlights tumor cell subtypes in patients with advanced prostate cancer

Abstract: Prostate cancer (PCa) clinical heterogeneity underscores tumor heterogeneity, which may be best defined by cell subtypes. To test if cell subtypes contributing to progression can be assessed noninvasively, we investigated whether 14 genes representing luminal, neuroendocrine, and stem cells are detectable in whole blood RNA of patients with advanced PCa. For each gene, reverse transcription quantitative polymerase chain reaction assays were first validated using RNA from PCa cell lines, and their traceability … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 50 publications
(146 reference statements)
0
6
0
Order By: Relevance
“…As cell patterns were shown to differ between adjacent foci, choosing tumor areas to build TMAs or dissecting cancer cells for further analysis may have substantial consequences. Nonetheless, our observation of different cell subtype patterns within a same patient and among patients is aligned with our recent report highlighting these cell subtypes in PCa transcriptomic datasets and the traceability and clinical relevance of PCa cell-subtype genes in liquid biopsies of mCRPC patients [59].…”
Section: Discussionmentioning
confidence: 99%
“…As cell patterns were shown to differ between adjacent foci, choosing tumor areas to build TMAs or dissecting cancer cells for further analysis may have substantial consequences. Nonetheless, our observation of different cell subtype patterns within a same patient and among patients is aligned with our recent report highlighting these cell subtypes in PCa transcriptomic datasets and the traceability and clinical relevance of PCa cell-subtype genes in liquid biopsies of mCRPC patients [59].…”
Section: Discussionmentioning
confidence: 99%
“…This minimally invasive approach may predict treatment resistance and outcome and improves therapeutic options. [5] Studies support the idea that prostate cell subtype genes are traceable in the blood of patients with advanced disease. Liquid biopsies were developed as an alternative to conventional tissue biopsies since they can be obtained in a noninvasive or minimally invasive way, thus avoiding the risks related to the collection of tissue biopsies and allowing serial sampling during the course of disease.…”
mentioning
confidence: 87%
“…Studies support the evidence that prostate cell subtype genes are traceable in the blood of patients with advanced disease. Data from over 1000 patients confirmed that overexpression patterns in the blood of 35 of 40 patients are best represented in metastases [5].…”
mentioning
confidence: 89%
See 2 more Smart Citations